2020
DOI: 10.1038/s41598-020-73090-4
|View full text |Cite
|
Sign up to set email alerts
|

Solvothermal synthesis of Fe3O4 nanospheres for high-performance electrochemical non-enzymatic glucose sensor

Abstract: Ferroferric oxide (Fe3O4) nanospheres have been synthesized via a facile solvothermal procedure to serve as an electrode material for high performance non-enzymatic glucose sensor. The as-synthesized Fe3O4 nanospheres with a uniform size from 16 to 18 nm, which can increase the reaction contact area and the active sites in the process of glucose detection. Benefiting from the particular nanoscale structure, the Fe3O4 nanospheres obviously enhanced the activity of electrocatalytic oxidation towards glucose. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The magnetite samples showed diffraction peaks attributed to Fe 3 O 4 ((JCPDS No. 03-0863) at 2θ of 30.3° (220), 35.4° (311), 43.4° (400), 53.5° (422), 56.9° (511), and 62.6° (440), , with a small diffraction peak at 2θ of 32° corresponding to α-Fe 2 O 3 . The nonmagnetic char of biomass and plastic only (PBC) did not show any diffraction lines related to Fe 3 O 4 , while the magnetic char composites of MBC and MPBC samples showed only diffraction lines for Fe 3 O 4 .…”
Section: Resultsmentioning
confidence: 99%
“…The magnetite samples showed diffraction peaks attributed to Fe 3 O 4 ((JCPDS No. 03-0863) at 2θ of 30.3° (220), 35.4° (311), 43.4° (400), 53.5° (422), 56.9° (511), and 62.6° (440), , with a small diffraction peak at 2θ of 32° corresponding to α-Fe 2 O 3 . The nonmagnetic char of biomass and plastic only (PBC) did not show any diffraction lines related to Fe 3 O 4 , while the magnetic char composites of MBC and MPBC samples showed only diffraction lines for Fe 3 O 4 .…”
Section: Resultsmentioning
confidence: 99%
“…After a clear solution was obtained, urea (3.0 g) and D-glucose (0.36 g) were added, and the mixture was stirred at room temperature for 30 min. Subsequently, the solution was transferred to a Teflon-lined stainless-steel autoclave and solvothermally treated at 200 • C for 12 h. Notably, previous works suggested that solvothermal temperatures of 160 • C and above are required to obtain a single phase of magnetite phase (Fe 3 O 4 ) [29,38,39], and the boiling point of ethylene glycol is elevated due to the elevated pressure in the reactor and the colligative property of solutions [40][41][42]. After cooling down to room temperature and washing sequentially with ultrapure water and ethanol (each three times), the resulting carbon-coated Fe 3 O 4 nanoparticles were magnetically separated from the solution using a neodymium magnet and dried at 60 • C in a vacuum oven (SHEL LAB, Shelton Manufacturing, Inc., Cornelius, Oregon) for 12 h. Uncoated Fe 3 O 4 nanoparticles were synthesized from a solvothermal treatment of a FeCl 3 /EG/urea mixture (without addition of D-glucose).…”
Section: Sample Preparationmentioning
confidence: 99%
“…Finally, the crucial materials, which determine the performance of the glucosesensing electrodes, would be the electroactive materials (Figure 6c-g). There are many types of electroactive material for the sensing of glucose by the electrochemical methods, such as (1) metal materials and (2) alloy materials [34][35][36][37][48][49][50]53,61,[125][126][127][128][129][130][131][132] (Figure 6c,d), (3) oxide materials and (4) hydroxide materials [39,40,51,52,54,55,58,59,[64][65][66][133][134][135][136][137][138][139] (Figure 6e,f), as well as ( 5) composite materials [38,[42][43][44][45][46][47]56,…”
Section: Systems Of Electroactive Materials For the Sensing Of Glucosementioning
confidence: 99%
“…In addition, the detection of the glucose concentration in the human physiological fluids could be simply accomplished by the facile electrochemical technique [64][65][66][67], which is utilized in cooperation with the non-enzymatic glucose electrodes. An illustration of the glucose concentration detection system via the electrochemical technique is shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%